Historical Arch Bridges-Deterioration and Restoration Techniques - Amin Bagherzadeh Azar; Ali Sari (Salehan Institute of Higher Education, 2023)
Historic buildings are the most valuable evidence of cultural heritage. They play an essential role in establishing a tangible link between the past and the present by understanding, interpreting, and tracing the epoch of civilization. Unfortunately, the high costs of restoration, vandalism, and arson take their toll. However, new technologies are having a positive impact on the restoration process and are becoming a suitable alternative to labor-intensive, expensive, and unsafe traditional inspections. Therefore, the role of non-destructive testing (NDT) as a new method is becoming more evident. Faro laser scanning, impact echo, impulse sound testing, and geoelectric tomography as non-destructive methods are leading to the inspection of historic structures to preserve their character. These new methods are representative of the development of non-contact techniques for the examination and documentation of structures. Non-destructive testing examines the internal and external structure of complex building components as well as defective areas, quantifies cracks, and detects near-surface moisture. The objective of this work is to identify new adventurous and traditional methods for the reconstruction of the Turkish arch bridges Dara-1 and Halilviran to determine the appropriate rehabilitation methods and their deterioration of construction materials, damage, and failure patterns. Bridge dimensions were measured using a Faro laser scanner, which allows inspectors to capture and evaluate data from bridges and structural components without permanently altering them. The laser captures bridge dimensions by scanning cross-sections of the structure in the horizontal and vertical planes. The data is exported in the form of point clouds that represent all visible aspects and actual dimensions of the bridge in 2D and 3D models. In comparison between traditional and laser scanning methods, the main advantages of the applied method are the time savings on-site and the creation of a three-dimensional model of the structure, which can be used to collect precise and accurate surface data of objects in a non-destructive manner.Â Doi: 10.28991/CEJ-2023-09-07-010 Full Text: PDF